Explosive Zunahme der häuslichen Krankenpflege bei Beatmeten und Tracheotomierten - Köhler, Dieter (DMW - Deutsche Medizinische Wochenschrift, 2019)
Since 2005, invasive long-term ventilation in Germany has increased significantly from around 1000 to 20 000 patients in Germany. Due to complex home care, the health care system incurs additional costs of around 4 billion euros per year. In addition, in the last 2 – 3 years more tracheostomized patients have been discharged home without ventilation (usually after stroke), and they receive the same complex home care. These patients have almost never been given the chance of a professional weaning trial by a weaning center. They are discharged from hospitals directly into the care. As a result, the quality of care is significantly worse than traditional care with structured discharge management via a weaning center. The solutions are difficult to find due to the interface problems between inpatient and outpatient care and the different organizational structures with different delivery systems. Possible solutions are shown, but most of them require a change in the law.
Keywords: invasive häusliche Beatmung; häusliche Krankenpflege; Kosten; Entlassmanagement